Técnicas de logoterapia para fortalecer la resiliencia de los estudiantes de décimo año de educación general básica paralelo b de la escuela 18 de noviembre periodo 2017-2018. - Pardo Ochoa, Diana Veronica (2018)
The thesis denominated: LOGOTHERAPY TECHNIQUES TO STRENGTHEN THE RESILIENCE OF THE STUDENTS OF THE TENTH YEAR OF BASIC PARALLEL EDUCATION "B" OF THE SCHOOL "NOVEMBER 18", PERIOD 2017-2018. The objective was to strengthen the resilience of the tenth year students of the basic general education "B" parallel, of the School "November 18", period 2017-2018, using logotherapy techniques. The research approach is quantitative; the design is pre-experimental, the methods they used were: scientific, descriptive, analytic-synthetic and inductive-deductive; As for the instrument, a Resilience Scale was used in a sample of 35 adolescents, of a non-probabilistic type. According to the results, it is known that 49% have a low level of resilience, 23% have medium resilience, 6% have a high level of resilience, and only 14% have high levels of resilience. When applying and evaluating the logotherapy techniques, it was deduced that the majority of adolescents increased their levels of resilience, so 17% maintain low levels, 11% average, 29% high average and finally 43% high levels, so it is recommended application of logotherapeutic techniques for the strengthening of resilience in adolescents.